A pH-Responsive Psyllium-Hyaluronic acid and Collagen based Hydrogel for Oral Insulin Delivery: pH-Responsive Hydrogel for Oral Insulin Delivery - Ahmad, Usman; Sami, Amtul Jamil; Noreen, Saadia`; Hussain, Ubaida; Khalid, Tanveer; Abdullah, Muhammad (Pakistan Journal of Health Sciences, 2023)
Diabetes mellitus is a chronic and heritable condition which grows adverse with date and eventually accelerates numerous difficulties such as end-stage renal disease, cardiac infections and vision problems. Objective: To highlight protein-based hydrogels as a contemporary focus in insulin delivery through the oral cavity. Methods: Novel hydrogels were formed in this study by using biomaterials (Psyllium, Hyaluronic acid and Collagen). The hydrogels were synthesized through a methodical process involving the combination of psyllium ispaghol husk, hyaluronic acid, and collagen for targeted insulin delivery. Initially, 1g of psyllium ispaghol husk was uniformly mixed with 200ml of distilled water. After achieving a homogeneous swelling, hyaluronic acid and collagen were added to the mixture. The synthesis of hydrogels was achieved by allowing the mixture to incubate at 38°C O/N. Physical characterization was done using FTIR analysis which indicates different bonding patterns. Results: Swelling ratio and drugs kinetics of hydrogels reveal maximum swelling and drug release at alkaline pH while minimum at acidic pH. Swelling kinetics shows that hydrogels followed less Fickian diffusion. These points favour the delivery of insulin in the intestine while escaping the acidic medium of stomach. Zone of inhibition around the hydrogels illustrated its antimicrobial activity. Finally, its administration to mice indicates the delivery of insulin by the decrease in glucose level measured by glucometer. Conclusions: Based on the diverse analyses conducted, it can be inferred that utilizing biomaterial-based hydrogels holds significant promise for effective insulin delivery through the oral route, especially beneficial for diabetic patients.